THE EFFECTIVENESS OF DIGITAL GAME BASED LEARNING ON STUDENTS’ WRITING SKILL BASED ON GENDER DIFFERENCES - Ratih Ayu Wulandari; Ulinuha Dahlina; Asih Rosnaningsih (Linguists : Journal of Linguistics and Language Teaching, 2025)
This study highlights the importance of preferences between male and female students that should be taken into account when designing digital game-based learning (DGBL) to improve writing skills. Until the present time, there were limited studies exploring gender differences among male and female students in using DGBL to teach narrative writing text. Thus, the purpose of this study is to examine the effect on students’ narrative writing skills enhanced through DGBL utilizing the Wordwall application, with an emphasis on gender differences. It employed a mixed-method design combining quantitative and qualitative techniques. A quasi-experimental design with a non-equivalent control group was utilized for the quantitative technique, while descriptive method was employed in the qualitative technique. The samples were selected purposively into different groups: experimental (XI Saintika 2 = 36 students) and control (XI Saintika 4 = 36 students). DGBL was utilized to teach narrative writing to the experimental group, whereas traditional techniques were employed to the control group. Students in the experimental group fared much better than those in the control group on both pre- and post-tests (M = 88.05 vs. 79.27), which was supported by t-test results (p < 0.05). It showed that by boosting motivation, engagement, and instant feedback, DGBL successfully improved writing performance. Even among normally passive students, Wordwall’s interactive elements encouraged active involvement. Although both male and female students benefited from DGBL, gender-based analysis showed that males were more competitive and females generally had more positive attitudes and structured writing styles. Teachers are required to design DGBL with various learning activities according to students’ individual differences to make sure all of them are involved actively during the teaching writing process.